KONSEP PENYUTRADARAAN TELEVISI KREATIF MELALUI PENDEKATAN UNSUR LOKAL NUSANTARA - Rembulan, Dara Bunga; Panindias, Asmoro Nurhadi (Seni Media Rekam ISI Surakarta, 2015)
Most of the Indonesian society form new interaction network with the western lifestyle, so indirectly it created the consumetive society in which everthing was consumed from foreign countries as the effects of the diffucion culture. That effects inflicted the Indonesian culture become eroded step by step. Therefore, creative director is needed for producing the television programme which can inform and distribute knowledge about diversity of Indonesian culture. In fulfilling these needs, the audio visual work was created with the emphasis on beauty shots of Indonesian culture, namely clip video exploration in temple surroundings, advertisement exploration of wayang and Indonesian cosmetic products. It is hoped that this television programme can educate the society on how to preserve the Indonesian culture and not easily influenced by foreign cultures.Keywords: creative, television, Nusantara, and directing